The effect of birth interval on fetal outcomes - Thapaliya, Rajeeb; Rai, BK; Bhandari, R; Rijal, P; Gupta, PP (Health Renaissance, 2016)
Background: Perinatal mortality includes both deaths in the first week of life and fetal deaths (stillbirths). Over 130 million babies are born every year, and more than 10 million infants die before their fifth birthday and almost 8 million before their first birthday. Objectives: To make an effort to find out impact of birth interval on fetal outcomes like, low birth weight (weight less than 2500 grams regardless of gestational age), perinatal death (death within 28 weeks of gestation to 7 days of birth) in subsequent pregnancies. Methods: This was a cross-sectional study conducted in BPKIHS, Dharan in 2011. Patients included were women of second gravida between age group 20 -35 years .The consecutive convenience sampling method was used to collect the data. Study population was divided into three birth interval groups of <18, 18-59,>59 months respectively and fetal outcomes (low birth weight, gestational age, early neonatal death, Apgar score) were compared. Results: Out of included population majority (55.63%) of the women had age range of 20-25 years with the mean age of 25.30. Among the total 168 who were included 20(11.91%) were belongs to birth interval <18 months, 113(67.26%) were found in 18-59 months group and 35(20.83%) were in >59 months group. Conclusion: There was increased risk of preterm and low birth weight and perinatal death in women with birth interval <18 months as compared to women with birth interval 18-59 months and groups >59 months. Health Renaissance 2015;13(3): 169-176